TRAGALDABAS: A new high resolution detector for the regular study of cosmic rays. (July 2015) - Alvarez-Pol, H; Blanco, A; Blanco, J J; Collazo, J; Fonte, P; Garzón, J A; Gómez, A; Kornakov, G; Kurtukian, T; Lopes, L; Morales, M; Morozova, A; et al.
Abstract: Research on cosmic rays is of big interest either for getting a better understanding about their origin and properties or because they offer very valuable information about the galactic, the solar and the Earth's environment. In order to improve our knowledge of all those fields, a high resolution cosmic ray tracking detector, TRAGALDABAS, is being commissioned at the Faculty of Physics of the Univ. of Santiago de Compostela (Spain). In this article we make overview of the main performances of the detector and we present some very preliminary results showing that the detector is taking good data, and that we are gathering a valuable sample of events, ready to be analyzed.